2014
DOI: 10.1080/13607863.2014.967170
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis associated behavioral and psychological signs and symptoms in mild cognitive impairment and Alzheimer's dementia

Abstract: AD patients clearly display psychosis associated BPSD, whereas MCI patients only display more severe frontal lobe symptoms and physically non-aggressive agitated behavior, but also less pronounced than in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Of note, a recent study in a Belgian cohort of patients with MCI and AD found that psychosis-related symptoms (such as delusions or hallucinations) were present in up to 40% of patients with AD. 16 In patient DR1090, the onset of memory problems was also preceded by mild parkinsonian features, which remained stable during the disease course under an unchanging dose of levodopa. A consensus diagnosis of AD was made, although the possibility of a concomitant Lewy body pathology could not be excluded.…”
Section: Discussionmentioning
confidence: 96%
“…Of note, a recent study in a Belgian cohort of patients with MCI and AD found that psychosis-related symptoms (such as delusions or hallucinations) were present in up to 40% of patients with AD. 16 In patient DR1090, the onset of memory problems was also preceded by mild parkinsonian features, which remained stable during the disease course under an unchanging dose of levodopa. A consensus diagnosis of AD was made, although the possibility of a concomitant Lewy body pathology could not be excluded.…”
Section: Discussionmentioning
confidence: 96%
“…This may restrict the representativeness of our findings, as such symptoms are relatively common in patients with dementia or MCI. 23 We believe that our results, using a simple and widely available task-oriented test, are sensitive to detect motor deficits in these populations. However, these results should be replicated in a longitudinal design.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic symptoms, such as hallucinations and paranoid/delusional ideation have been reported in up to 45% of the non-DS AD patients -delusions being generally more common than hallucinations (Eustace et al, 2002;Gauthier et al, 2010;Mega et al, 1996;Van der Mussele, Mariën, et al, 2014b). Using the BEHAVEAD, Temple & Konstantareas (2005) studied BPSD in AD patients with DS (DS-AD) and without (AD-only).…”
Section: Psychosis Hallucinations Paranoia and Delusionsmentioning
confidence: 99%